Relevansi Pendidikan Akhlak Said Nursi di Sd Muhammadiyah Kreatif Kraksaan - Firyal Rafidah Lesmana; Fathor Rohim; Fahrudin Mukhlis (Syntax Corporation, 2023)
This study explains the relevance of Said Nursi's moral education at SD Muhammadiyah Kreatif Kraksaan which has its own way of instilling moral education to students by doing good habituation, personal approach, school environment and approach to family. In particular, this study focuses on the moral education of students, with the aim of knowing in educating the next generation of the nation, in order to create good morals. The analytical method used in this study is a qualitative approach. In this study, secondary data were conducted through various sources. The results collected through case studies are interpretive to describe education in SD Muhammadiyah Kreatif Krakaan. The results of the study are compiled systematically. According to Said Nursi, there are three moral education, including the cultivation of the value of beauty and majesty, inner education, and combining the values of religion and science. That way, education becomes a decisive aspect for the progress of human civilization. Said Nursi was born in 1293 Rumi, in the village of Nurs and Said Nursi had the ability in the field of religious science as well as non-religious science. Nursi was given the nickname